Structural planning, development and analysis of in silico pharmacokinetic properties of salicylic acid analogues for cosmetic purposes - Rômulo Barros dos Santos; Wendy Fernanda Sales do Vale; Charllyton Luís Sena da Costa (Estação Científica, 2017)
Cosmetic formulations containing hydroxy acids (HAs) have been used in clinical practice for decades to treat a variety of skin conditions. Salicylic acid, the most prominent representative used in this class, has been used as an exfoliant or keratolytic agent, and in the treatment of fine lines and wrinkles, skin pigmentation, dandruff, seborrheic dermatitis, acne and to improve the general aesthetic appearance of the skin. In view of this, the present research aimed to develop in silico analogs of salicylic acid for cosmetic purposes, through the characterization of its physicochemical, pharmacokinetic and pharmacodynamic properties of the drugs developed. The developed compounds, as well as the reference molecules, were analyzed in ACD / ChemSketch software’s, MarvinSketch version 5.9.0, PreADMET version 2.0 and SpartanStudent for Universities. Among the substances used for molecular increase, retinoic acid and its retinol and retinal derivatives were more relevant, besides the use of urea, serine, lactic acid, palmitic acid, recinolytic acid and norbixin. The molecular planning allowed the development of 35 molecules called RWC. Thus, it was possible to verify through the analysis that the great majority of the molecules created had similarity to the molecules of the retinoid group, which implies that these presented excellent results in view of the objective of said study.